Elizabeth Price, Fiona Tan, Zimoun: Assembly. New Media Gallery, New Westminster, BC - Seller, Shyla (Archivaria, 2022)
Elizabeth Price, Fiona Tan, Zimoun: Assembly. New Media Gallery, New Westminster, BC. September 18 – December 5, 2021. Curated by Sarah Joyce and Gordon Duggan.